Evaluation of the factors related to dental anxiety in North Indian population: a questionnaire study - Singh, Iqbal; Bhat, Nitish; Kaur, Robindera; Thakur, Kalpna; Nandan, Hemwati; Bhardwaj, Nandini (International Journal Of Community Medicine And Public Health, 2020)
Background: To evaluate the factors affecting dental anxiety level on the basis of a questionnaire in the North Indian Population. Methods: A questionnaire based on the various factors related to dental anxiety was formulated and distributed among the various regions of the north India. We got response from 250 people, the data was then analysed and results were formulated. Results: Out of 450 questionnaires which were distributed, a total of 400 questionnaires were received. Overall high prevalence of dental anxiety i.e. 85% was noted. More increased values for anxiety were seen for people younger than 30 years (70%), compare to that of elder people (30%). Females seem to have greater anxiety levels as compared to males (p value >0.000). Among 450 people 176 had visited clinics previously with 98 having bad experience (55.6%) and 78 people having a relatively good past dental experience (44.2%). Conclusions: Anxious patients are often more difficult to treat, therefore the questionnaire proved beneficial in estimating factors related to dental anxiety. Young people, women and those having negative dental experience had the highest anxiety levels.